Enhancement of initial shear modulus in cement and fly ash admixed Bangkok clay out of bender element test - Sakol Pochalard; Kitti Promsang; Chalermpon Wungsumpow; Keeratikan Piriyakul (Discover Sustainability)
Abstract This article aims to investigate the initial shear modulus development in Ordinary Portland Cement (OPC) and Fly ash (FA) admixed Bangkok clay. The role of cement is to stabilize and enhance the compressive strength of Bangkok soft clay. The OPC is replaced by FA which is a sustainable method since FA is an industrial waste product from Mae Moh power plant in the northern of Thailand. Bangkok soft clay was mixed with OPC content of 20% by weight and varied FA content from 0, 10, 15, 20, 25 to 30% by weight, after curing periods of 7, 14, 28 and 90 days. The initial shear modulus (G0) was determined from the shear wave velocity (Vs) measured by non-destructive bender element testing. For comparison and ensuring the results, the strength development of the tested clay samples was also determined by destructive unconfined compression test (UCS). From the results, it was found that the optimum of replacement fly ash is about 15–20% and showed that the strength development of this Bangkok clay admixed with OPC and FA is increased with increasing the curing time. Moreover, the research found the linear relationship between G0 (MPa) and qu (MPa) as G0 = 275.65 qu. Last but not least, the linear relationship between the normalized G0/G0(28) and the qu/qu(28) was noted as G0/G0(28) = 0.9526 qu/qu(28).